Patient X-ray exposure and ALARA in the neonatal intensive care unit: Global patterns - Amber J. Gislason-Lee (Elsevier, 2021)
A literature review was conducted to determine norms for practice in neonatal intensive care units (NICU) around the world, given the harmful risks associated with radiation exposure at a very young age; risk of radiation-induced harm later in life increases with every X-ray image taken, more so for younger premature babies. Empirical studies including a measurement of radiation dose in a NICU, published after the year 2000 in a peer-reviewed journal, were collected. Measured doses to patients or X-ray phantoms, number of X-rays per stay and conclusions with recommendations made in response to these values were compared for 25 studies from around the world. The number of X-rays a patient underwent during a NICU stay ranged from 0 to 159. Younger, lower birth weight patients consistently had the greatest number of X-rays per stay. Recommended action based on measured dose ranged from extensive (to minimize risk to neonates) to minimal (to reduce risk) to none (because imaging benefits outweigh patient risk), with no consistent pattern linking recommended action with dose quantity. This demonstrates a broad range of interpretations of the As Low As Reasonably Achievable (ALARA) concept. These findings indicate a disparity in the response to neonatal X-ray dose concerns on a global scale, posing a public health risk to this particular neonatal population. More up-to-date imaging protocols and dose limits specifically for the NICU environment with standardized dose monitoring would help minimize this risk to achieve the public health goals of prevention and harm reduction.